Catastrophic injuries in pole-vaulters - Boden, B. P.; Pasquina, P.; Johnson, J.; Müller, F. O. (The American Journal of Sports Medicine, 2001)
Pole vaulting is a unique sport in that athletes often land from heights ranging from 10 to 20 feet. We retrospectively reviewed 32 catastrophic pole-vault injuries that were reported to the National Center for Catastrophic Sports Injury Research between 1982 and 1998. The purpose of this study was to determine the mechanisms of injury so that preventive strategies can be implemented. Information was obtained by means of a telephone interview with someone familiar with the accident. Allinjuries occurred in male athletes at an average age of 17.5 years; 31 were catastrophic head injuries and 1 was a thoracic spine fracture that resulted in paraplegia. Three common mechanisms were identified: 17 (53%) athletes landed with their body on the landing pad and their head on the surrounding hard ground, 8 (25%) landed in the vault box after being stranded at the height of the jump, and 5 (16%) completely missed the landing pad. The mechanism of injury in the remaining two athletes was unknown. The accident resulted in death in 16 (50%) athletes and in permanent disability in 6 (19%). Increasing the minimum landing pad size and enforcing the rule requiring soft surfaces adjacent to the landing pads are the primary recommendations for preventing injuries. The authors discuss other rule and equipment changes that may help reduce the occurrence of future injuries.